Connectome Analysis in an Individual with SETD1B-Related Neurodevelopmental Disorder and Epilepsy. Issue 6 (6th August 2022) - Weng, Rosa; Nenning, Karl-Heinz; Schwarz, Michelle; Riedhammer, Korbinian M.; Brunet, Theresa; Wagner, Matias; Kasprian, Gregor; Lehrner, Johann; Zimprich, Fritz; Bonelli, Silvia B.; Krenn, Martin
Abstract : This article has supplementary material on the web site: www.jdbp.org . ABSTRACT: Objective: Causative variants in SETD1B, encoding a lysine-specific methyltransferase, have recently been associated with a neurodevelopmental phenotype encompassing intellectual disability, autistic features, pronounced language delay, and epilepsy. It has been noted that long-term and deep phenotype data are needed to further delineate this rare condition. Methods: In this study, we provide an in-depth clinical characterization with long-term follow-up and trio exome sequencing findings to describe one additional individual affected by SETD1B -related disorder. The diagnostic workup was complemented by a functional magnetic resonance imaging (fMRI) study. Results: We report a 24-year-old male individual with an early-onset neurodevelopmental disorder with epilepsy due to the de novo missense variant c.5699A>G, p.(Tyr1900Cys) in SETD1B (NM_015048.1). He exhibited delayed speech development, autism spectrum disorder, and early-onset epilepsy with absence and generalized tonic-clonic seizures. Despite profoundly impaired communication skills, ongoing improvements regarding language production have been noted in adulthood. fMRI findings demonstrate abnormal language activation and resting-state connectivity structure. Conclusion: Our report expands the previously delineated phenotype of SETD1B -related disorder and provides novel insights into underlying disease mechanisms.